Of Walden Pond : Henry David Thoreau, Frederic Tudor, and the Pond between - Cline-Ransome, Lesa (Holiday House, 2022)
"The story of Henry David Thoreau's time at Walden Pond is contrasted with businessman Frederic Tudor's scheme to cut 180 tons of ice from Walden Pond and transport it to India"--